Implementasi Fungsi Hash dalam Kriptografi Modern untuk Enkripsi Data Satu Arah - Winanda, Mirza; Defrianti, Serli; Nabila, Wulan; Rikarni, Rikarni; Alfarizhi, Habieb (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
Cryptography is the science and art used to maintain data privacy. In its development, modern cryptographicalgorithms work by processing data in the form of a series of bits. One important approach in cryptography is the useof a one-way hash function (one-way hash function), which is able to change data into a fixed representation thatcannot be returned to its original form.This paper discusses the implementation of hash functions in modern cryptography for the one-way encryptionprocess. The hashing application is developed using the Python programming language with the hashlib library and aTkinter-based GUI interface. This application allows users to enter text, select a hash algorithm such as MD5, SHA1, SHA-256, SHA-512, and HSE, and get the hash results directly. Tests were carried out on several algorithms totrigger differences in the length and complexity of the results.The main characteristic of a one-way hash function is that two different messages will always produce different hashvalues. The test results show that each algorithm produces a unique hash value for a given input, with varying lengthsdepending on the algorithm used. SHA-512 produces the longest hash and is considered the most secure among otheralgorithms.